Pengaruh Gender, Persepsi, Motivasi dan Pengetahuan Perpajakan Terhadap Minat Berkarir di Bidang Perpajakan (Studi Empiris Mahasiswa Prodi Akuntansi Universitas Islam Malang dan Universitas Muhammadiyah Malang) - Silvia Qotru Nada; Maslichah Maslichah; Junaidi Junaidi (Universitas Islam Malang, 2023)
This study aims to determine the effect of gender, perception, motivation and knowledge of taxation on interest in a career in taxation. Sampling in this study used purposive sampling and slovin techniques. The process sed data is primary data obtained from the distribution of Google Form links and obtained by 86 respondents who have met the criteria. The method used is multiple linear regression analysis. The results show gender does not affect the interest in a career in the field of taxation, while the perception, motivation, and knowledge of taxation has a positive effect on the interest in a career in the field of taxation in Accounting Students at the Islamic University of Malang and University of Muhammadiyah MalangKeywords: Gender, perception, motivation, tax knowledge, career interest.